Prospects for the development of community-based care in remote rural areas: a stakeholder analysis in Laos - Marco Liverani; Khampheng Phongluxa; Koukeo Phommasone; Rusheng Chew; Arjun Chandna; Tiengkham Pongvongsa; Mayfong Mayxay; Sengchanh Kounnavong; Elizabeth Ashley; Yoel Lubell (BMC, 2024)
Abstract Background Community-based health programmes have been a cornerstone of primary care in Laos for decades. The study presented here aimed to document prospects for the development of current programmes, considering perceptions about health and health care priorities in the communities, implementation challenges, the policy landscape and opportunities associated with the availability of new technologies. Methods The research design primarily involved qualitative in-depth interviews with stakeholders (n = 35) responsible for the planning, management, or implementation of community-based care in Laos at different levels of the health system. These included health managers at central departments or institutes of the Ministry of Health, provincial health departments, district health offices, heads of health centres, village health volunteers, community representatives, and international stakeholders. Results There was consensus that service delivery is still a challenge in many areas, due to geographic inaccessibility of health facilities, communication barriers, health-seeking behaviour, trust, and gender discrimination, particularly among ethnic minorities. In these settings, community health workers have the potential to extend the reach of the formal health system, acting as cultural brokers across sectors of society, ethnicities, and worldviews. To maximise impact, planners need to carefully consider the implementation model, financing arrangements, health system integration, and changing health priorities in the communities. Conclusions This study examined challenges to, and opportunities for, the expansion and health system integration of community-based care in Laos. Further development and horizontal integration of community-based care remains a complex financing and governance challenge, although the renewed emphasis on primary care and the ongoing process of decentralisation provide a favourable policy environment in the country to sustain and potentially expand existing programmes.